Penerapan Sistem Informasi Terpadu dalam Industri Tape Desa Banjarsari Menggunakan Celestial Cartography sebagai Peta Navigasi Kunjungan - Alby Aruna; Eka Putri Surya; Mohamad Firzon Ainur Roziqin; Abdul Rahman Prasetyo; Adinda Marcelliantika; Ginanjar Atma Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of an integrated information system in the tape industry in Banjarsari Village using Celestial Cartography as a navigation map aims to enhance efficiency and visitor experience. This program integrates information technology with digital navigation to provide accurate and interactive guidance for visitors. The methods used include the development of a digital map application, technical training for industry managers, and evaluation of system effectiveness through user feedback. The results show increased visitor satisfaction and more efficient visit management. The implementation of this integrated information system is expected to support the development of a more modern and attractive tape industry in Banjarsari Village.